Large-scale structure of the fast solar wind - Bisi, M. M.; Fallows, R. A.; Breen, A. R.; Habbal, S. Rifai; Jones, R. A. (Journal of Geophysical Research: Space Physics, 2007)
We present the results of a comprehensive study of the fast solar wind near solar minimum conditions using interplanetary scintillation (IPS) data taken with the EISCAT system in northern Scandinavia, and a recent extremely long baseline observation using both EISCAT and MERLIN systems. The results from IPS observations suggest that the fast wind inside 100 solar radii (R-circle dot) can be represented by a two-mode model in some cases but this distinction is much less clear by in situ distances beyond 1 astronomical unit (215 R-circle dot). Two distinct fast streams are seen in the extremely long baseline IPS observation; comparison of the IPS line of sight with a synoptic map of white light indicates the faster mode overlies the polar crown and the slower fast mode overlies an equatorial extension of the polar coronal hole.